أنماط الأسرة خصائصها، واقعها أهم العوامل المحددة لحجم الأسرة في سورية خلال (1994، 2009) - الغرير موسى; سويد ريما (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تحتل الأسرة مكانة أساسية في تنمية المجتمع وتطويره وتحسين رفاهيته، وإن تبيان خصائصها وأنماطها وأثرها في السلوك الإنجابي يعد من أهم الموضوعات التي تحتاج إلى دراسة ومناقشة لمعرفة دورها المؤثر على معدل النمو السكاني بالاستناد إلى بعض البيانات الإحصائية الضرورية التي تشكل القاعدة العلمية لرسم السياسات الاقتصادية والاجتماعية التي تهدف إلى تمكين الأسرة و تلبية متطلباتها. وبناء على ذلك سيتم في هذا البحث دراسة دور الأسرة السورية واقعها وتطورها من خلال إلقاء الضوء على حجمها وأهم العوامل المؤثرة في ذلك، ودراسة التباين والاختلاف في حجمها على مستوى المحافظات، ومستوى الريف والحضر، إضافة إلى دراسة البنية التركيبية لأرباب الأسر وبيان أثر ذلك في عدد الأولاد، معتمدين في دراستنا على عرض لبعض المؤشرات والعلاقات الإحصائية التي تبين مدى العلاقة بين بعض العوامل الاجتماعية والاقتصادية وعدد الأولاد في الأسرة و كيفية التأثير في ذلك. توصلت الدراسة إلى وجود علاقات ارتباط ذات دلاله إحصائية بين المتغير التابع (عدد الأولاد) وعدد من المتغيرات المستقلة (المستوى التعليمي والمهني للزوج، وللزوجة، والعمر عند الزواج الأول للزوجة، واستخدام وسائل تنظيم الأسرة) وقد اختلف أثر العلاقة باتجاهه وقوته (موجب وسالب)، وذلك حسب المتغير المستقل وعلاقته بالمتغير التابع، كما بينت الدراسة مدى قدرة المتغير المستقل على تفسير المتغير التابع، وخلصت الدراسة إلى مجموعة من النتائج والتوصيات وعرض للمصادر التي اعتمدت عليها. The family occupies a key position in the development of society and the improvement of well-being, and to describe the family’s characteristics, patterns and their impact on reproductive behavior is one of the most important topics that need to be examined and discussed to see its effect on population growth rate based on some statistical data necessary to form the scientific base for economic and social policy which aims to empower the family and their needs. Accordingly, this research will examine the role of the evolution and reality of the Syrian family by highlighting the most important factors affecting its size, contrasting and studying the difference in size at the provincial level and at the level of rural and urban areas. It also studies the structure of households and the number of children in our study, relying on some indicators and statistical relations which show the relationship between social and economic factors and the number of children in the family and how to influence it. The study found a statistically significant link between the dependent variable (number of children) and a number of independent variables (Educational and professional level of the husband, wife, age at first marriage to wife, and using family planning methods) the direction and strength of the relationship was differed in its direction and strength (positive and negative), according to the independent variable and its relation to the dependent variable. The study also showed the extent to which the independent variable interpreted the dependent variable. The study was concluded by a set of findings and recommendations and a display of the sources that has adopted.